2009
DOI: 10.1002/jgm.1331
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinduction by microbubble‐enhanced transcutaneous sonoporation of human bone morphogenetic protein‐2

Abstract: These results suggest the possibility of the effective clinical use of human BMP-2 gene therapy using transcutaneous sonoporation, and should facilitate clinical applications of BMP-2 gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 34 publications
(34 reference statements)
1
42
1
Order By: Relevance
“…It is known that rhBMP-2 can induce the differentiation of non-osteogenic cell lines into osteoblastic cells, indicating that the BMP-2 gene could be transfected into C3H10T1/2 cells with an ultra-fine needle to induce the differentiation of fibroblast into osteoblast. Our previous studies demonstrated that implantation of rhBMP-2 with a carrier matrix [14], in vivo adenovirus-mediated gene transfer [15], and in vivo plasmid DNA-mediated gene transfer, such as electroporation [16], sonoporation [11], or repeat plasmid injection [17], could cause osteoinduction. However, the above techniques showed some limitations in practical usage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that rhBMP-2 can induce the differentiation of non-osteogenic cell lines into osteoblastic cells, indicating that the BMP-2 gene could be transfected into C3H10T1/2 cells with an ultra-fine needle to induce the differentiation of fibroblast into osteoblast. Our previous studies demonstrated that implantation of rhBMP-2 with a carrier matrix [14], in vivo adenovirus-mediated gene transfer [15], and in vivo plasmid DNA-mediated gene transfer, such as electroporation [16], sonoporation [11], or repeat plasmid injection [17], could cause osteoinduction. However, the above techniques showed some limitations in practical usage.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous attempts have been made to overcome the relatively low transfection efficiency, including the application of electric pulses and / or ultrasonic devices. Although these techniques are efficient to some degree, using a large amount of plasmid DNA is needed to enhanced the effect [11,17]. In addition, direct injection of naked plasmid DNA into the animal or human body is associated with toxicity and immunogenicity [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(50) Sonoporation with 75 µg BMP-2 plasmid led to radiographic bone formation in a mouse intramuscular model, although pDNA without sonoporation also led to some ectopic bone in this study. (51) Multiple cycles of injections and sonoporations were required to induce bone. (51) Electroporation similarly allows cellular internalization of pDNA after plasma membrane integrity is compromised by electrical pulses.…”
Section: Bmp9mentioning
confidence: 99%
“…(51) Multiple cycles of injections and sonoporations were required to induce bone. (51) Electroporation similarly allows cellular internalization of pDNA after plasma membrane integrity is compromised by electrical pulses. (52) Electroporation of 25 to 50 µg BMP-2/7 plasmid yielded radiopaque bone in a rat intramuscular model.…”
Section: Bmp9mentioning
confidence: 99%